Chromosomal rearrangement interferes with meiotic X chromosome inactivation - Homolka, David; Ivanek, Robert; Capkova, Jana; Jansa, Petr; Forejt, Jiri (Genome research, 2007)
Heterozygosity for certain mouse and human chromosomal rearrangements is characterized by the incomplete meiotic synapsis of rearranged chromosomes, by their colocalization with the XY body in primary spermatocytes, and by male-limited sterility. Previously, we argued that such X-autosomal associations could interfere with meiotic sex chromosome inactivation. Recently, supporting evidence has reported modifications of histones in rearranged chromosomes by a process called the meiotic silencing of unsynapsed chromatin (MSUC). Here, we report on the transcriptional down-regulation of genes within the unsynapsed region of the rearranged mouse chromosome 17, and on the subsequent disturbance of X chromosome inactivation. The partial transcriptional suppression of genes in the unsynapsed chromatin was most prominent prior to the mid-pachytene stage of primary spermatocytes. Later, during the mid-late pachytene, the rearranged autosomes colocalized with the XY body, and the X chromosome failed to undergo proper transcriptional silencing. Our findings provide direct evidence on the MSUC acting at the mRNA level, and implicate that autosomal asynapsis in meiosis may cause male sterility by interfering with meiotic sex chromosome inactivation.
Keywords: down regulace; inaktivace chromozomu X; Male; Infertility, Male; genová přestavba; spermatogeneze; umlčování genů; myši kongenní; translokace genetická; mužské pohlaví; Meiosis; Spermatogenesis; chromozom X; chromatin; X Chromosome; Chromatin; Mice, Congenic; meióza; Animals; Down-Regulation; lidé; spermatocyty; Spermatocytes; Gene Rearrangement; Humans; zvířata; X Chromosome Inactivation; myši inbrední C57BL; myši; Translocation, Genetic; Mice, Inbred C57BL; Gene Silencing; Mice; mužská infertilita